Andragogi Profetik: Telaah Konsep Pendidikan Orang Dewasa Perspektif Hadis - Vina Najariah; Ernawati Erniwati; Muhammad Alif (Al-Mu'tabar, 2025)
Andragogy, defined as the art and science of teaching adults, is an educational approach that emphasizes learner autonomy, experience, needs, and motivation. In the practice of Islamic education, the educator (teacher) becomes one of the key components in effectively applying these principles. The perspective of hadith highlights that lifelong learning and the appreciation of life experience are integral parts of Islamic education. This study aims to explain the concept of adult education based on hadiths and to explore the andragogical principles that can be applied within Islamic educational practice. This research employs a qualitative approach using content analysis of relevant hadiths. The findings reveal that adult learning in Islam prioritizes an experience-based approach, addresses the actual needs of learners, and builds internal motivation to learn. Furthermore, the importance of patience, respect for experience, and effective communication are essential factors for success in educating adults, whose cognitive processes differ from those of children. This study develops the concept of "prophetic andragogy" as a model of transformative education grounded in prophetic values.